Personalized tutoring: ChatGPT as a virtual tutor for personalized learning experiences - Ariza Flores, Víctor André (2023)
This study aimed to ascertain what factors influence the length of time undergraduates receive individual tutoring. Quantitative questionnaires with Likert scale items gathered data on perception, satisfaction, engagement, self-confidence, preference for individualized instruction and participation in decision-making. The sample consisted of 247 University of Lima students. Among the quantitative methods used to examine the data were reliability and validity tests, correlations, analysis of variance, and regression. In tests of reliability, all variables exhibited fair to excellent internal consistency. The results disclosed severalsignificant statistics that shed light on the variables that influence the duration of personalized tutoring. 68.8 percent of participants reported using ChatGPT for personalized tutoring, while 31.2 percent did not. The majority of students utilized personalized tutoring for two to five semesters. Regardinggender, males compriseda larger proportion of the sample(62.3% versus 37.7%) than females. Several recommendations can be made based on these findings. Priority number one is increasing user satisfaction through more efficient and effective individualized tutoring sessions. It canincrease student engagement by utilizing multimedia and interactive teaching aids. The study emphasizes the significance of attending to the emotional and psychological aspects of individualized tutoring to enhance student experiences and outcomes.